Properties and applications of new superlattice: twisted bilayer graphene. (June 2019) - Wang, J.; Mu, X.; Wang, L.; Sun, M.
Abstract: Two-dimensional (2D) materials have different physical and chemical properties from bulk materials. Single-layer 2D materials are stacked vertically similar to Lego blocks to form van der Waals heterostructures (VdWHs), and the properties of 2D materials will also change dramatically. When a single layer of graphene is stacked together to form bilayer graphene, just like vdWHs, especially when the lattice of the upper and lower layers is twisted, the superlattice is formed. The novel electronic structure gives rise to innovative electrical properties, optical properties, and so on. The studies and applications of twisted bilayer graphene (TwBLG) have become a popular topic. This report reviews the properties and recent applications of superlattice based on TwBLG. Graphical abstract: Image 1 Highlights: Two-dimensional (2D) materials have different physical and chemical properties from bulk materials. Single-layer 2D materials are stacked vertically similar to Lego blocks to form van der Waals heterostructures, and the properties of 2D materials will also change dramatically. When the lattice of the upper and lower layers is twisted, the novel electronic structure gives rise to innovative electrical, optical properties, and so on. The studies and applications of twisted bilayer graphene have become a popular topic.